(3GdJWhQ GdSjGSj hGdOSJhQj aj Gdjef GdOjebQGWjI GdTYHjI (B:s (3ef YGe (B1937 (3MJi bjGe LeghQjI Gdjef GdLfhHjI GdTYHjI ai (B30 (3fhaeHQ (B1967 / s - (3YeQ YHO Gddg HGeMShfs; (3YHOGdMejO ceGd MTjTs; (3eMehO GdSbGs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQIs (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 1981)
(3jSJgd gPG GdHMK HebOeI YGeI jJHjf ajgG ehVY YOf hGSJQGJjLjI gPG GdehbY hGdEQJHGW GdJGQjNj Hjf YOf hGdefGWb GdJj chfJ eY YOf LeghQjI Gdjef GdLfhHjI GdTYHjI hGdLeghQjI GdYQHjI GdjefjI, Ke GdOhd GdbOjeI GdJj bGeJ ai gPg GdefWbI aj GdYUQ GdLGgdj Ke CUd GdOhd GdYQHjI GdLfhHjI hWHjYI fXGe GdMce ajgG Ke JfJbd GdOQGSI Edi HGH JegjOj jYQV ajg GdfXGe GdSjGSj hGdOSJhQj aj GdeMejI GdZQHjI hGdTQbjI eY ebOeI JGQjNjI Yf GdefWbI GdZQHjI hJSdd GdGSJYeGQ GdHQjWGfj EdjgG YGe (B1938(3, Ke EQJHGW GdefWbI GdZQHjI HeYGgOGJ MeGjI hGSJTGQI; eeG CKQ Ydi eQcRgG GdbGfhfj, ceG jYGdL gPG GdHGH GdfXGe GdSjGSj hGdOSJhQj aj eMejI YOf GdTQbjI hGdUQGY Ydi GdSdWI aj MVQehJ gPG, hjJfGhd GdbSe GdChd ef GdOQGSI GdfXGe GdSjGSj hGdOSJhQj ai OSJhQ YOf (B6391 (3eY OQGSI GdChVGY GdSjGSjI hGdGLJeGYjI bHd gPG GdOSJhQ Ke GdChVGY GdJYdjejI hGdGbJUGOjI aj YOf (B6391 -8591(3, hCNjQG WQb GdESJjdGA Ydi GdCbGdje GdeSJYeQg, CeG GdbSe GdKGfj ef GdOQGSg ajJfGhd fXGe GdMce HOSJhQ YOf (B2691 (3hPdc HHMK GdJWhQGJ GdSGHbI dUOhQ gPG GdOSJhQ, Ke jfbSe GdbSe GdKGfj Edi HGHjf jYGdL ChdgeG GdNUGFU GdYGeI dOSJhQ YOf (B2691 (3HjfeG jNJU GdHGH GdKGfj HOQGSI GdSdWI GdJfajPjI hGdJTQjYjI hPdc ai HGHjf jYGdL ChdgeG GdJfXjeGJ GdSjGSjI hGdCMRGH, HjfeG jJfGhd GdHGH GdKGfj SbhW GdOSJhQ hGdfXGe GdSjGSj, hCNjQG JCJj GdNGJeg dJYQV Jbjje OhQ HQjWGfjG ef gPg GdJWhQGJ GdOSJhQjg hJCKjQ GdChVGY GdGLJeGYjI HefWbI YOf hGdeMejGJ Ydi GdJWhQGJ GdOSJhQjg(B.s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdYGe (B1981. s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B621-644.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3GdfXGe GdOSJhQj GdYOfj s; (3Gdjef GdOjebQGWjI GdTYHjIs; (3GdfXGe GdSjGSj hGdOSJhQj s; (3MGce GdeMejIs; (3GJMGO GdLfhH GdYQHjs; (3GdSdWI GdbVGFjI GdYdjG s; (3ehGfY GdJQTjM s; (3bGfhf GdGfJNGH GdYOfj s; (3GdHjFI GdGfJNGHjIs; (3GdGeJjGRGJ hGdMUGfGJ GdHQdeGfjIs; (3fXGe GdMce HOSJhQ YOfs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes